Harmonisasi dan keselarasan hidup dalam cerpen Harta Gantungan karya Ahmad Tohari - Khasanah, Venus; Prakoso, Teguh (Universitas Mulawarman, 2023)
Kang Nurya's persistence in preserving buffalo as the hanged treasure is the center of the story discussed in the